The complete plastid genome sequence of Viola selkirkii Pursh ex Goldie (Violaceae) - Ah-reum Go; Kyeong-Sik Cheon; Ki-Oug Yoo (Mitochondrial DNA. Part B. Resources, 2022)
Viola selkirkii, belonging to the genus Viola, has heart-shaped leaves and pale purple flowers, and it is widely distributed in the Northern Hemisphere, including Europe, North America, and Asia. In this study, the plastid genome of V. selkirkii was sequenced and phylogenetic analysis was performed on 11 Viola plastid genomes. The length of the plastid genome length of V. selkirkii was 156,774 bp, and it was identified as having a typical quadripartite structure with a large single-copy region (85,930 bp), a small single-copy region (17,982 bp), and two inverted repeat regions (26,431 bp each). A phylogenetic analysis was conducted with 77 protein-coding genes from the complete plastid genomes of 11 Viola and nine Salicaceae species; the complete plastid genome of Erythroxylum novogranatense was used as an outgroup. Viola formed a monophyletic clade, and V. selkirkii was closely related to V. ulleungdoensis. These results contribute to the clear identification of the phylogenetic position of V. selkirkii in Viola.